2022
DOI: 10.1021/acs.inorgchem.2c01659
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Structural Phase Transition, Anomalous Insulator-to-Metal Transition, and n–p Conduction-Type Switching in Defective, NiAs-Type Cr1−δTe

Abstract: Cr1−δTe, as a unique series of defective compounds with a NiAs-type structure and periodic metal vacancies, has attracted intensive research interest because of its diversity in structure and property dependent on the tunable stoichiometric ratio. Another feature of these compounds is their ability to switch between NiAs- and MnP-type structures, in which there often exist composition-, temperature-, or pressure-induced phase transitions accompanied by intriguing physical property switching. Herein, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
3
6
0
Order By: Relevance
“…Localization of carriers can usually lead to an abnormal increase in resistivity under HP. Similar phenomena have been found in Cr 5 Te 8 and MnBi 2 Te 4 . , By the measurements of Hall resistivity, it is observed that the carrier mobility is significantly decreased, which means that the carrier is more localized under HP, thus causing the resistivity increase upon compression. Such intercalated compounds with periodic vacancies seem to be prone to pressure-induced carrier localization.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Localization of carriers can usually lead to an abnormal increase in resistivity under HP. Similar phenomena have been found in Cr 5 Te 8 and MnBi 2 Te 4 . , By the measurements of Hall resistivity, it is observed that the carrier mobility is significantly decreased, which means that the carrier is more localized under HP, thus causing the resistivity increase upon compression. Such intercalated compounds with periodic vacancies seem to be prone to pressure-induced carrier localization.…”
Section: Resultssupporting
confidence: 77%
“…This atomic-shift-type (i.e., martensitic) phase transition always leads to abrupt changes in both the electrical and magnetic properties of materials. Previous HP research studies on the Cr–Te system have shown that derivative NiAs-type compounds tend to retain their initial structures under HP but exhibit electronic transitions upon compression . Herein, we focus on the Cr–Se system and present the synthesis and HP studies of two chromium selenides, CrSe and Cr 2 Se 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the result of pressure-induced p-n switching. [80] The photothermal effect is another important mechanism for achieving IPC under high pressures. Generally, the resistance of metallic materials increases linearly with the light-induced increase in temperature, which contributes to IPC.…”
Section: Pressure Engineering For Ipcmentioning
confidence: 99%
“…As an important thermodynamic parameter as temperature, pressure can remarkably modulate the crystal structures and physical properties of materials by changing crystallographic parameters such as bond length and bond angle . Under high pressure (HP), the materials can exhibit a series of binary conversions of physical properties, such as spin-crossover, , piezochromism, , and metal–insulator transition. , In addition, pressure-driven n – p switching has also gradually attracted research interest, which mainly occurs in materials such as elements, , metal oxides, , chalcogenides, and pnictides. , Among them, there is one class of pressure-driven n – p switching that essentially originates from electronic transitions, typically as the Fermi surface topological changes known as Lifshitz transitions, e.g. , in Bi 2 Te 3 , while the other class is related to pressure-induced structural phase transitions, e.g.…”
Section: Introductionmentioning
confidence: 99%